The systems thinker analytical skills - Rutherford, Albert (Independently published, 2019)
The Systems Thinker ? Analytical Skills aims to raise the level of your mental performance by focusing on the fundamentals of how to use your mind effectively. This book will show you how to:?Increase your ability to analyze problems and to comprehend what you read, hear, experience in a logical manner. ?Examine the logical structure of good and bad reasoning. ?Look at what type of evidence are decisions commonly based on.?Detect common fallacies and rhetorical and psychological factors that can influence your thinking. The book presents the methods that good problem solvers use in understanding complex ideas. It provides practice in applying these methods to a variety of comprehension, analytical, and reasoning questions. It also includes a number of logical thinking problems to hone your logical thinking skills.
Keywords: Systems